META-ANALYSIS: EFFECTIVENESS OF PROJECT-BASED LEARNING ON STUDENT CREATIVITY - Widiarini, Putu; Anak Agung Istri Agung Rai Sudiatmika; Ketut Suma; Suardana, I Nyoman (Universitas Pendidikan Ganesha, 2024)
This research is quantitative research with meta- analysis methods. The aim of this research is to describe the effectiveness of the project learning model on student creativity. The research sample consisted of 10 articles in the accredited national journal Sinta. All articles are the result of research on physical learning in the science group at the high school level. The data analysis technique used is calculating the effect size value. Based on the results of the meta- analysis, it was found that the average total effect size value was 1.55 with a standard deviation of 0.83, which was in the very high category. This shows that the problem-based learning model is effective in increasing student creativity. The results further show that the project-based learning model is also effective at various levels of high school and various physics subject matter.